The V223I substitution in hemagglutinin reduces the binding affinity to human-type receptors while enhancing the thermal stability of the H3N2 canine influenza virus - Liu, Liling; Wang, Fujun; Wu, Ying; Mi, Weiyong; Zhang, Yaping; Chen, Lei; Wang, Dongxue; Deng, Guohua; Shi, Jianzhong; Chen, Hualan; Kong, Huihui (Frontiers in Microbiology, 2024)
Given the intimate relationship between humans and dogs, the H3N2 canine influenza viruses (CIVs) pose a threat to public health. In our study, we isolated four H3N2 CIVs from 3,758 dog nasal swabs in China between 2018 and 2020, followed by genetic and biological analysis. Phylogenetic analysis revealed 15 genotypes among all available H3N2 CIVs, with genotype 15 prevailing among dogs since around 2017, indicating the establishment of a stable virus lineage in dogs. Molecular characterization identified many mammalian adaptive substitutions, including HA-G146S, HA-N188D, PB2-I292T, PB2-G590S, PB2-S714I, PB1-D154G, and NP-R293K, present across the four isolates. Notably, analysis of HA sequences uncovered a newly emerged adaptive mutation, HA-V223I, which is predominantly found in human and swine H3N2 viruses, suggesting its role in mammalian adaptation. Receptor-binding analysis revealed that the four H3N2 viruses bind both avian and human-type receptors. However, HA-V223I decreases the H3N2 virus's affinity for human-type receptors but enhances its thermal stability. Furthermore, attachment analysis confirmed the H3N2 virus binding to human tracheal tissues, albeit with reduced affinity when the virus carries HA-V223I. Antigenic analysis indicated that the current human H3N2 vaccines do not confer protection against H3N2 CIVs. Collectively, these findings underscore that the potential threat posed by H3N2 CIVs to human health still exists, emphasizing the necessity of close surveillance and monitoring of H3N2 CIVs in dogs.